Salivary Nitric Oxide Levels in Adults with Different DMFT Scores in a Selected Iranian Population: A Cross-Sectional Study - Mahsa Esfehani; Zahra Keshavarzi; Monirsadat Mirzadeh; Marayam Tofangchiha; Francesco Pagnoni; Rodolfo Reda; Luca Testarelli (University of Zagreb. School of Dental Medicine, 2023)
Objectives: Due to the emphasis on the protective and antimicrobial role of Nitric Oxide against gas-trointestinal diseases, investigating its relationship with dental caries is a right topic. Therefore, this research has investigated the amount of saliva Nitric Oxide in different volumes of DMFT indicator in adults. Material and Methods: In this descriptive- analytical cross-sectional study, 80 participants (20-35 years old), without a history of systemic disease and drug use participated as research sam-ples, (53.8% of the participants in the study were women). Participants were selected from patients who had visited dental Department. The participants were divided in four groups based on DMFT (DMFT=0, 1≤DMFT≤3, 3<DMFT<10, DMFT≥10). Non-stimulating saliva was collected from all partici-pants between 9-11 am in a calibrated tube. Saliva Nitric Oxide was measured using a Nitrous Oxide test, based on the Griess reaction. We used a correlation test to analyze quantitative variables, and t-test or ANOVA for qualitative and quantitative variables. Results: A significant relationship between DMFT and age was identified. At different levels of DMFT, significant relationship between DMFT and sex was not found. In different groups of DMFT, no significant relationship between Nitric Oxide and DMFT exist. Conclusion: The level of Nitric Oxide saliva was not affected by the amount of DMFT.